2016
DOI: 10.1080/03019233.2016.1156243
|View full text |Cite
|
Sign up to set email alerts
|

Charging composition and structure optimisation in the sintering process (Part I)

Abstract: In this paper, an optimisation system for charging composition and structure in the sintering process was established in order to reduce the sinter cost in the ironmaking process. The system comprised four modules: sinter metallurgical performance testing and analysis, sintering burdening design and optimisation, sintering matching calculation, and sinter component and property prediction. The data for the first module came from actual production values of a steelworks and from testing in the laboratory. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Through the control of the blast furnace load distribution process, the stable operation of the blast furnace was realized, and the production index of the blast furnace was optimized [9]. WANG and others developed a mathematical model for sintering structure and composition optimization during sintering process, which made it possible to optimize sintering structure [10]. Nath and others have optimized the quality of sinter and improved the utilization rate of fuel by using a genetic algorithm [11].…”
Section: Introductionsmentioning
confidence: 99%
“…Through the control of the blast furnace load distribution process, the stable operation of the blast furnace was realized, and the production index of the blast furnace was optimized [9]. WANG and others developed a mathematical model for sintering structure and composition optimization during sintering process, which made it possible to optimize sintering structure [10]. Nath and others have optimized the quality of sinter and improved the utilization rate of fuel by using a genetic algorithm [11].…”
Section: Introductionsmentioning
confidence: 99%
“…[1][2][3] The number, size, composition, morphology, and spatial distribution of nonmetallic inclusions in steel have a crucial impact on the cleanliness and performance of the steel product. [4][5][6][7][8] Particularly, large and long MnS inclusions precipitated during heat treatment after rolling of the steel and have a detrimental effect on the strength and corrosion resistance of heavy rail steels. [9][10][11][12][13] Many studies were reported to control large-sized MnS inclusions according to the characteristic and source of MnS in the steel, such as slag refining, [14,15] calcium/magnesium addition, [16][17][18][19] zirconium/cerium addition, [20][21][22] heat treatment process, [23,24] and heterogeneous nucleation improvement.…”
mentioning
confidence: 99%